2018
DOI: 10.1002/ajmg.a.38831
|View full text |Cite
|
Sign up to set email alerts
|

Two Angelman families with unusually advanced neurodevelopment carry a start codon variant in the most highly expressed UBE3A isoform

Abstract: We present three children from two unrelated families with Angelman syndrome (AS) whose developmental skills are far more advanced than any other non-mosaic AS individual ever reported. All have normal gait and use syntactic language spontaneously to express their needs. All of them have a c.2T > C (p.Met1Thr) variant in UBE3A, which abrogates the start codon of isoform 1, but not of isoforms 2 and 3. This variant was maternally inherited in one set of siblings, but de novo in the other child from the unrelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…A study in which specifically the cytosolic mUBE3A-Iso2 was deleted in mice, showed no behavioral phenotypes and changes in synaptic function, and the behavioral deficits of AS mice could be fully recapitulated by selective deletion of the nuclear mUBE3A-Iso3 isoform ( 9 ). Recently three individuals with AS have been described who specifically lack the nuclear hUBE3A-Iso1 ( 15 ). Based on the isoform localization, we determined in this study, we would predict that this mutation causes a loss of most of the nuclear UBE3A and that the cytosolic UBE3A levels remain the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in which specifically the cytosolic mUBE3A-Iso2 was deleted in mice, showed no behavioral phenotypes and changes in synaptic function, and the behavioral deficits of AS mice could be fully recapitulated by selective deletion of the nuclear mUBE3A-Iso3 isoform ( 9 ). Recently three individuals with AS have been described who specifically lack the nuclear hUBE3A-Iso1 ( 15 ). Based on the isoform localization, we determined in this study, we would predict that this mutation causes a loss of most of the nuclear UBE3A and that the cytosolic UBE3A levels remain the same.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a third human UBE3A isoform has been reported (hUBE3A-Iso2), which has no homologue in mice ( 14 ). Similar to mice, loss of the most abundantly expressed short isoform (hUBE3A-Iso1) in human results in a AS-like phenotype ( 15 ), but the localization of this human isoform has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…One of UBE3A's salient molecular features is its shift from the cytoplasm to nucleus upon neuronal maturation Dindot et al, 2008;Gustin et al, 2010), likely driven by shifts in isoform expression (LaSalle et al, 2015;Miao et al, 2013;Sadhwani et al, 2018). Importantly, it was recently shown that mice lacking nuclear UBE3A show electrophysiological and behavioral deficits similar to other AS model mice that lack maternal UBE3A (Avagliano Trezza et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, although start codon variants are often associated with a severe disease course, 10,11 there are several reports of disease causing start codon variants describing a milder phenotype. [12][13][14] The residual protein synthesis in case of such a start codon variant may be explained by the production of a shorter but still partly functional protein because of the use of an alternative downstream start codon, either in the mutated transcript itself or in alternatively spliced transcripts. The CLN3 protein is known to exist in multiple isoforms, of which a few have a putative later start position-recently extensively reviewed by Mirza et al 6and thus do not encompass the mutated c.1A > C base pair as present in our patients.…”
Section: Discussionmentioning
confidence: 99%